2020
DOI: 10.1186/s40360-020-00446-x
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of a dual PI3-kinase/mTOR inhibitor BEZ235 in adult patients with relapsed or refractory acute leukemia

Abstract: Background Combined inhibition of phosphatidylinositol 3-kinase (PI3K) and the mammalian target of rapamycin (mTOR) complexes may be an efficient treatment for acute leukemia. The primary objective of this phase I single center open label study was to determine the maximum tolerated dose (MTD) and recommended phase II dose (RP2D) of the dual pan-class I PI3K and mTOR inhibitor BEZ235 in patients with advanced leukemia. Methods Herein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
(70 reference statements)
2
12
0
Order By: Relevance
“…Dactolisib (BEZ235) is a dual pan-PI3K and mTOR inhibitor for which a phase I study in acute leukemia showed positive effect in a subset of ALL patients. 39 However, digestive toxicity (mostly dose-dependent) remains an important problem. MK2206, an allosteric pan-AKT inhibitor, has been shown to induce apoptosis and autophagy in T-ALL cell lines and primary patient samples.…”
Section: Discussionmentioning
confidence: 99%
“…Dactolisib (BEZ235) is a dual pan-PI3K and mTOR inhibitor for which a phase I study in acute leukemia showed positive effect in a subset of ALL patients. 39 However, digestive toxicity (mostly dose-dependent) remains an important problem. MK2206, an allosteric pan-AKT inhibitor, has been shown to induce apoptosis and autophagy in T-ALL cell lines and primary patient samples.…”
Section: Discussionmentioning
confidence: 99%
“…There are no new clinical trials of BEZ235 developed on solid tumors. Some acute lymphoblastic leukemia patients may have some alterations in the PI3K/AKT/mTOR signaling pathway, and BEZ235 had promising effects in this small subset of patients [ 165 ]. AML did not benefit from BEZ235 treatment.…”
Section: Inhibitors Of the Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…Considering that most dose-limiting toxicities such as fatigue, diarrhea, nausea, and mucositis were noted with both PI3K and mTOR inhibitors, it is not unexpected that pan-PI3K and mTOR inhibition resulted in a high prevalence of adverse events at the dose of 400 mg/day. On the other hand, 300 mg/day was far better tolerated by the patients; therefore, this dose was established as recommended for phase II studies [ 115 ]. It is worth noting that dactolisib was found to increase the incidence of grade 3–4 adverse events in evaluable patients in several other clinical studies [ 116 ].…”
Section: Signaling Pathways Contribute To Glucocorticoid Resistance I...mentioning
confidence: 99%